Three new species of Neoplecostomus (Teleostei: Siluriformes: Loricariidae) from the Upper Rio Paraná basin of southeastern Brazil - Roxo, Fábio F.; Oliveira, Claudio; Zawadzki, Cláudio H. (Zootaxa, 2012)
In this study, we describe three new species of the genus Neoplecostomus: N. bandeirante, from Salesópolis in the stateof São Paulo, N. langeanii from Muzambinho, in the state of Minas Gerais, and N. botucatu from Botucatu, in the state ofSão Paulo. All of the described species are found in the Upper Rio Paraná basin. The new species are different from eachother and from their nominal congeners in their mitochondrial DNA sequences (COI), morphology and meristic traits, inaddition to their color patterns. Morphologically, N. bandeirante can be distinguished from all congeners by the presenceof moderate keels throughout the lateral series of plates and by a naked area between each mid-ventral and ventral platethat is greater in size than the length of these plates. Neoplecostomus botucatu is morphologically distinguished by a re-duction of the adipose fin and the presence of dark spots that are distributed along the body. Neoplecostomus langeaniican be morphologically distinguished by the absence of hypertrophied odontodes and a swollen integument on the head, as well as by morphometric characteristics.Key-words: catfishes, freshwater fishes, molecular identification, Neoplecostominae, Neotropical fishes, taxonomyNo presente estudo, descrevemos três novas espécies do gênero Neoplecostomus: N. bandeirante de Salesópolis, no estadode São Paulo, N. langeanii de Muzambinho, no estado de Minas Gerais e N. botucatu de Botucatu, no estado de São Paulo.Todas as espécies descritas são da bacia do Alto Rio Paraná. As novas espécies são diferenciadas por sequências de DNAmitocondrial (COI), morfologia e caracteres merísticos, adicionalmente por aspectos de coloração. Morfologicamente, N.bandeirante é diferenciada das congêneres principalmente pela presença de quilhas moderadas ao longo das séries de pla-cas laterais e área nua entre cada placa médio ventral e ventral maior que o comprimento dessas placas. Neoplecostomusbotucatu é diferenciada morfologicamente pela redução da nadadeira adiposa e presença de pintas escuras em todo o cor-po. Neoplecostomus langeanii pode ser distinguida morfologicamente pela ausência de odontódeos hipertrofiados e pele intumescida na cabeça, tanto quando por caracteres morfométricos.